2017
DOI: 10.1089/scd.2016.0204
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine Activity from Adipose-Derived Stem Cells on In Vitro Wound Healing in Human Tympanic Membrane Keratinocytes

Abstract: Stem cell therapies for tympanic membrane repair have shown initial experimental success using mesenchymal stem cells in rat models to promote healing; however, the mechanisms providing this benefit are not known. We investigated in vitro the paracrine effects of human adipose-derived stem cells (ADSCs) on wound healing mechanisms for human tympanic membrane-derived keratinocytes (hTM) and immortalized human keratinocytes (HaCaT). ADSC conditioned media (CM) were assessed for paracrine activity on keratinocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 82 publications
3
20
2
Order By: Relevance
“…There are various mechanisms for improving the effects of stem cells in AD. It had been confirmed that AD-SCs could have therapeutic effects by mediating paracrine signaling of angiogenesis, inflammation, cell homing, and cell survival (26,29,30). The ADSCs administration presented raised levels of growth factors like basic fibroblast growth factor (bFGF), vascular endothelial growth factor (VEGF), nerve growth factor (NGF), and neurotrophic factors such as glial-derived neurotrophic factor (GDNF) and brain-derived neurotrophic factor (BDNF) (16,31,32).…”
Section: Discussionmentioning
confidence: 98%
“…There are various mechanisms for improving the effects of stem cells in AD. It had been confirmed that AD-SCs could have therapeutic effects by mediating paracrine signaling of angiogenesis, inflammation, cell homing, and cell survival (26,29,30). The ADSCs administration presented raised levels of growth factors like basic fibroblast growth factor (bFGF), vascular endothelial growth factor (VEGF), nerve growth factor (NGF), and neurotrophic factors such as glial-derived neurotrophic factor (GDNF) and brain-derived neurotrophic factor (BDNF) (16,31,32).…”
Section: Discussionmentioning
confidence: 98%
“…MSC acellular derivatives are being rigorously investigated as a means to accelerate the proliferation, migration and differentiation of keratinocytes and dermal fibroblasts, in order to regulate the complex interactions that occur during wound healing [123,167,168]. Scratch assays revealed that, relative to the control (medium with serum), dermal fibroblasts and keratinocytes enhanced their rate of wound closure when exposed to MSC acellular derivatives by increasing their migration instead of their proliferation rates [167].…”
Section: Stimulation Of Proliferation and Migration Of Local Keratinomentioning
confidence: 99%
“…Human adipose-derived stem cells (ADSCs) are multidirectional differentiation potential stem cells extracted from adipose tissue. ADSCs can migrate to a damaged site and differentiate into skin appendages to repair damaged skin through their multidirectional differentiation potential [5][6][7][8]. At the same time, ADSCs can secrete various growth factors to inhibit the inflammatory response, accelerate wound angiogenesis, and promote wound healing [9].…”
Section: Introductionmentioning
confidence: 99%